LOCAL NATURAL RESOURCES FILLER IN MAKING OF RADIATOR CAP SEAL VULCANIZED - Hari Adi Prasetya (Jurnal Dinamika Penelitian Industri, 2017)
Activated charcoal palm shell can be used as a filler in the manufacture of vulcanized cap seal radiator. Palm shell charcoal is a waste processing of palm oil and renewable resources. This research aimed to determine the effect of activated charcoal palm shell on the mechanical properties of the vulcanisate radiator cap seal and to obtain the best concentration to prevent the hardening of the radiator cap seal. The effect of activated charcoal palm shell consentrations (35, 45, 55 and 65 phr, respectively) on the hardness, tensile strength, elongation et break, ageing resistance (change of hardness, tensile strength, elongation et break) and tear resistance were evaluated. The experimental research used non Factorial Completely Randomized Design and each treatments was replicated three times. The results showed that the best properties fullfilled the requirements of commercial radiator cap seal was using of 45-55 phr of activated charcoal palm shell. This range showed the mechanical properties of: 68-71 Shore A in hardness, 131-139 N/mm2 in tensile strength, 447-450 % for elongation at break, with no significant difference before and after ageing, and 40-42 kg/cm for the tear resistance.